Oral Microbiota Analysis of Tissue Pairs and Saliva Samples From Patients With Oral Squamous Cell Carcinoma – A Pilot Study - Yang, Ke; Wang, Yuezhu; Zhang, Shizhou; Zhang, Dongsheng; Hu, Lihua; Zhao, Tengda; Zheng, Huajun (Frontiers in Microbiology, 2021)
Oral microbiota dysbiosis is associated with the occurrence and progression of oral cancer. To investigate the association between the microbiota and risk of oral squamous cell carcinoma (OSCC), we identified the microbial composition of paired tumor (TT)/paracancerous tissues (NPT) and saliva (TS) samples in OSCC patients through 16S rRNA gene sequencing. A total of 22 phyla, 321 genera, and 869 species were identified in the oral samples. Paired comparisons revealed significant differences between TT, NPT, and TS groups, with the genus Filifactor significantly enriched in TT. The phylum Actinobacteria; genus Veillonella; and species Granulicatella adiacens, Streptococcus sanguinis, and Veillonella rogosae were significantly enriched in NPT, while the phylum Bacteroidetes; genera Capnocytophaga, Haemophilus, and Prevotella; and seven species, including Capnocytophaga sp., Haemophilus sp., and Neisseria sp., were significantly enriched in TS. In tumor tissues, the abundance of Prevotella intermedia was profoundly higher in the gingiva, while Capnocytophaga gingivalis and Rothia mucilaginosa were enriched in the lining mucosa and tongue. Increasing in abundance from the early tumor stage to the late stage, Solobacterium moorei in TT and Campylobacter sp. strain HMT 044 in TS were positively correlated with OSCC development, suggesting that bacteria were selected by different microenvironments. The correlation between 11 microbial species and 17 pathway abundances was revealed, indicating the potential function of low-abundance bacteria. Overall, our analysis revealed that multiple oral bacterial taxa are associated with a subsequent risk of OSCC and may be used as biomarkers for risk prediction and intervention in oral cancers.